Accuracy of Writing Diagnosis and Accuracy of Gastroenteritis Codes - Heltiani, Nofri; widyawati, Dwi; -, Andriansyah (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Accurate diagnosis coding according to ICD-10 to assign accurate diagnosis codes for inpatients also requires additional information such as laboratory results to be taken into account. The results of initial observations made on 10 medical resume sheets for gastroenteritis cases showed that 3 (30%) had accurate diagnosis codes and 7 (70%) had inaccurate diagnosis codes. This can affect the quality of data, information and reports as well as the accuracy of rates for general patients and INA-CBG'S rates which are used as a payment method for BPJS patients so that it can have an impact on reducing the quality of hospital services. This research aims to determine the accuracy of writing diagnoses and the accuracy of gastroenteritis codes for inpatients at Rafflesia Hospital in 2023. The type of research used is descriptive research with a cross sectional method. The population in this study was 214 medical record files for inpatient gastroenteritis cases in 2022 with a sample of 140 files using a simple random sampling technique. The research data used is secondary data which was processed univariately. The results of this study were that from 140 inpatient gastroenteritis medical record files, 100(100%) had the results of supporting examinations but they did not match the diagnosis written on the patient's medical resume because in writing the diagnosis it was not stated whether the gastroenteritis was infected or non-infected, 29(21% ) writing the diagnosis correctly, 43(31%) wrote the diagnosis incorrectly because they used Indonesian and 68(48%) wrote the diagnosis incorrectly because they used non-standard abbreviations and 69(49%) had an accurate diagnosis code and 71(51%) Inaccurate diagnosis code because there is no 4th character.